2022
DOI: 10.3389/fped.2021.785440
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Dietary Habits and MTHFD1 Gene Polymorphisms With Ventricular Septal Defects in Offspring: A Case-Control Study

Abstract: ObjectivesThis study aimed at assessing the association between maternal methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) gene polymorphisms, maternal dietary habits, and their interactions with the risk of ventricular septal defects (VSD) in offspring.MethodsFrom November 2017 to March 2019, a case-control study comprising 360 mothers of VSD cases and 504 mothers of healthy infants was conducted in Han Chinese populations. The main exposures of interest were maternal dietary habits in early pregnancy and MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Song and colleagues aimed at assessing the association between maternal methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) gene polymorphisms, maternal dietary habits in early pregnancy, and their interactions with the risk of ventricular septal defects (VSD) in offspring. By comparing mothers of VSD cases and mothers of healthy infants, they observed significant interaction effects between maternal dietary habits and genetic SNPs of the maternal MTHFD1 gene at rs1950902, rs2236225, and rs2236225 on the risk of VSD [49].…”
Section: Abnormal Embryonic Developmentmentioning
confidence: 99%
“…Song and colleagues aimed at assessing the association between maternal methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) gene polymorphisms, maternal dietary habits in early pregnancy, and their interactions with the risk of ventricular septal defects (VSD) in offspring. By comparing mothers of VSD cases and mothers of healthy infants, they observed significant interaction effects between maternal dietary habits and genetic SNPs of the maternal MTHFD1 gene at rs1950902, rs2236225, and rs2236225 on the risk of VSD [49].…”
Section: Abnormal Embryonic Developmentmentioning
confidence: 99%
“…Finally, Song et al ( 380 ) reported that after adjusting for 10 potentially confounding variables, maternal intake during early pregnancy of several foods, one of which was soy, was associated with a reduced risk of ventricular septal defects (VSDs) in the offspring. The highest intake category was consumption ≥6x/wk.…”
Section: Isoflavone-related Topicsmentioning
confidence: 99%